Assessment of Ornamental Plants Tolerance for Acute Exposure of Acetaminophen and Methylparaben in Constructed Wetlands- a Preliminary Study - Mutar, Zahraa Hasan; Mohammed, Ahmed A.; Abdulwahab Al-Baldawi, Israa; Abdullah, Siti Rozaimah Sheikh; Ismail, Nur ’Izzati (Al-Khwarizmi Engineering Journal, 2022)
The study aims to select suitable ornamental plant species that can survive relatively with high concentrations of acetaminophen and methylparaben in constructed wetlands. Alternanthera spp, Asparagus aethiopicus and Chlorophytum comosum are examined to withstand three initial concentrations, 20, 100 and 200 mg/L of acetaminophen and methylparaben. A total of 21 plastic pails with each 3 L capacity consisting of nine pails are used for each pharmaceutical and personal care products (PPCPs) compounds (acetaminophen and methylparaben) for three ornamental plants (Alternanthera spp, Asparagus aethiopicus and Chlorophytum comosum), with three pails as plant controls. The results reveales that both Alternanthera spp and Chlorophytum comosum exhibite a good tolerance for acetaminophen with a reduction in the total chlorophyll content of about 4.4–12.3% and 3.9–31.9% for Alternanthera spp and Chlorophytum comosum, respectively. Moreover, it is evident that high concentrations (100 and 200 mg/L) of methylparaben adversely affects the chlorophyll content of the three involved plant species. These results indicate that ornamental plants play an important role in the phytoremediation of PPCPs and can be considered as an esthetic treatment for hospital wastewater.